Óleo de buriti e babaçu na composição da dieta de ovinos - GOMES, Ruan Mourão da Silva (2018)
The objective of this study was to evaluate the dry matter and nutrients digestibility of the diets, as well as to determine the ruminal parameters, in confined lambs submitted to diets containing buriti and babassu oil. 21 castrated sheep, ½ Santa Inês x ½ Dorper, with an approximate age of 6 months and average live weight of 26±4 kg were used. The animals were distributed in unbalanced blocks, with three treatments and seven replicates, being four blocks, three with two replicates of each treatment and one block with one repetition. The experimental period was constituted of 17 days for adaptation and 4 for data collection, totaling 21 days. The collection of feces was done using individual collection bags, and on the last day of the experimental period the ruminal fluid was collected with the aid of a vacuum pump and a probe. Addition of burti and babassu oil in the confined lambs diet altered the dry matter intake (P= 0.03), being the highest consumption for diet without addition of oils (998.82 g/day), followed by diet containing buriti oil (872.62 g/day). Intake and digestibility of the ethereal extract were altered (P = 0.03) by the addition of oils to the diets. Higher intake was observed in the diets with oils (52.82 g/day) for babassu oil and (60.59 g/day) for buriti oil. The digestibility of ethereal extract was higher in the diet containing babassu oil (80.92%) compared to buriti oil (73.21%). In relation to the ruminal parameters, it was possible to observe effect of the experimental diets only for pH, propionate, isobutyrate, butyrate, isovalerate and relation to cetate: propionate. The addition of buriti and babassu oil in the sheep diet affects dry matter intake, however, it does not alter nutrient digestibility and ruminal parameters. Based on this, the indication of use is associated with the performance results, acquisition costs and quality aggregation to the final product.